Systematic review: The Effect of Non-pharmacological Interventions on Reducing Pain During the First Stage of Labor - Adita Kusfaningrum; Sri Rejeki; Rahayu Astuti (Indonesian Journal of Global Health Research, 2025)
Labor pain is one of the main problems experienced by mothers during the birth process. Pain management can be done with pharmacological and non-pharmacological methods. Non-pharmacological approaches are considered safer and more effective because they have minimal side effects. This systematic review aims to analyze the effect of non-pharmacological interventions such as music therapy, endorphin massage, effleurage massage, deep back massage, and a combination of therapies on reducing pain in the first stage of labor. The review method uses a systematic review using PRISMA For Systematic Review, which is obtained from the Google Scholar, Proquest, Pubmed databases. The review results obtained 18 of the 369 articles selected from 2018-2025. The keywords used are non-pharmacological therapy, labor pain, music therapy, massage therapy. Labor pain is grouped into 1 theme, namely non-pharmacological therapy. This study involved 18 relevant articles. The results showed that all interventions were effective in reducing labor pain (p <0.05). Combinations of therapies such as music and aromatherapy provided a more significant effect.